Met and Unmet Expectations for Breast Reconstruction in Early Posttreatment Breast Cancer Survivors. Issue 4 (October 2017) - Steffen, Laurie E.; Johnson, Aimee; Levine, Beverly J.; Mayer, Deborah K.; Avis, Nancy E.
Abstract : The purpose of this study was to evaluate the prevalence of met and unmet expectations after breast reconstruction among breast cancer survivors following mastectomy. A secondary objective was to examine reasons women report their experiences of reconstructive surgery were better or worse than expected. As part of a larger study of breast cancer survivors, participants completed self-administered questionnaires within 8 months of diagnosis and at 6, 12, and 18 months later. At the 18-month follow-up, women who had breast reconstruction were asked whether their reconstruction was better, the same, or worse than expected. The sample consisted of 130 survivors (mean age = 48.5 years) who had breast reconstruction following mastectomy and completed the 18-month follow-up, 42% of whom reported their reconstruction was worse than expected and only 25% reported it was better. Most frequently reported reasons for reconstruction being worse than expected were related to appearance of the reconstructed breast and pain. A high percentage of patients with breast cancer undergoing breast reconstruction following mastectomy reported the results as worse than expected, with the primary reasons for dissatisfaction related to the feel and appearance of the reconstructed breast. Patients with breast cancer considering breast reconstruction need better preoperative education or understanding about what to expect from reconstruction.